The correct doctrine and its impact on the behavior of the individual and society between rooting and contemporary: A Descriptive Study - Noman, Sajid Sabri (Journal of Islamic Sciences, 2019)
The Islamic nation has never been able to protect their ideas and minds because of the spread of many kinds of corruption in values, morals and balances, as well as religious beliefs and beliefs, which carry within its superstitions, delusions and fantasies, not to mention the unjust laws and laws. This study aims at showing the impact of faith on the behavior of the individual and reforming him to stand up against the enemies of Islam, who were able, with great skill and great cunning, to achieve what they want. They came with glamorous titles such as civilization and civilization, progress and development.The doctrine has a clear impact on addressing such brilliant headlines, and their impact on building the proper behavior of the individual to create a conscious and cultured society based on true legitimacy and awakening the moral conscience within the individual and society. This is in fact an extension of the building of the human conscience, Normal humanity ".
Keywords: true belief; behavior of the individual and society; psychological stability